Generalization of Foreign Experience in the Career Guidance Center Work of Urfu - Polozov, Ð.A. (Budapest International Research and Critics University, 2020)
The subject of the work was to improve the methodology of the career guidance center of the URFU (Yekaterinburg, Russia) by overcoming contradictions in the recommendations on the profiles of activities for people with different types of personality. An adequate recommendation is based on combination of the generalized opinion of experts (12 career centers at the US universities, authors of 8 books) on the profile of the applicant's activity (manager, agent, etc.) and 24 fields of activity. Due to this solution it was possible to evaluate each sphere for the applicant by saturation with suitable profiles. And it extremely increases his chances to realize the most significant project by the age of 39. The methodology was based on the typological concept of the personality structure from the personality type, the character type and the dominant type of intelligence. This concept in contrast with the five-factor model of the personality structure demonstrates a significant result of the work. About 70% of graduates of the Russian universities do not work on the received specialty. For 7 years the presented methodology of the vocational guidance center of the URFU (Yekaterinburg, Russia) was improved to the level at which these